2005
DOI: 10.1080/00222930500533443
|View full text |Cite
|
Sign up to set email alerts
|

A biogeographical analysis of the tenebrionid beetles (Coleoptera, Tenebrionidae) of the island of Thasos in the context of the Aegean Islands (Greece)

Abstract: This research aimed to study the origin and the biogeographical relationships of the tenebrionid beetle (Coleoptera, Tenebrionidae) fauna of the island of Thasos, with reference to the other Aegean Islands. A total of 32 Aegean Islands and 170 taxa (species and subspecies), 23 of which occur on Thasos, were included in this study. Nine tenebrionid species are here reported for the first time from Thasos, including the first records of Platydema europaeum and Nalassus plebejus from the Aegean Islands. Several m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 65 publications
3
59
0
2
Order By: Relevance
“…Taxonomic treatment and data concerning species distribution are the same as in Fattorini & Fowles (2006). As a whole, 170 taxa (138 species and 32 subspecies) were ascertained to occur as native populations on the study islands.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Taxonomic treatment and data concerning species distribution are the same as in Fattorini & Fowles (2006). As a whole, 170 taxa (138 species and 32 subspecies) were ascertained to occur as native populations on the study islands.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Fattorini & Fowles 2006). On the Aegean Islands, several tenebrionid species are represented by different subspecies endemic to individual islands or groups of islands.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flather (1996), who applied six different models to species-accumulation curves based on bird occurrences from roadside stops, reported that the Weibull distribution and the beta-P distribution produce the best fit. Fattorini & Fowles (2005) applied 10 different models to SARs of beetle species on Greek islands and have reported that the power model and the Weibull distribution produced the best fits. Fattorini (2007), who applied five models plus a linearized power model to the distribution of butterflies in Europe, reports the linearized power function and the Archibald logistic (which he calls the 'He-Legendre model') produces the best fit.…”
Section: Asymptotic Modelsmentioning
confidence: 99%
“…Connor & McCoy 1979;Rosenzweig 1995;Williamson et al 2001Williamson et al , 2002Fattorini & Fowles 2005) studies showed that SARs can be most often modelled by a simple power function: S5CA z , where S is the species number in a given area A, and C and z are the parameters of the model, with C being an estimate of the mean number of species per unit area and z is a scaling coefficient that ranges frequently between 0.1 and 0.3. Also, this allometric function is simple to fit and the only one whose parameters can be assigned a biological meaning.…”
Section: Introductionmentioning
confidence: 99%